Pengaruh Penggunaan Media Flash Card Math terhadap Hasil Belajar Metematika - Kokom Komalasari (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The experiment research was conducted in the tenth grade in Vocational High School Mahadika, Ciracas, East Jakarta, academic year 2013/2014, the aim of this experiment research is to know the effect of media flash card math on mathematics achievement. True experiment design was used in this research in the form of posttest only control design. Sample was consists of experiment group and control group which was taken randomly, two classes was taken from three paralel class. After giving different treatments for two groups, then giving the posttest with the instrument that consist of 28 items in multiple choice form and 5 alternative answers.  The instrument has been tested and validation empirically. Analysis of research data descriptive and inferential, which inferentially using the "test" , by first testing the assumption of normality and homogeneity of variance. The results showed that there are significant effect of using media flash cards math on mathematics achievement.